Hearing in Noise With Unilateral Versus Bilateral Bone Conduction Hearing Aids in Adults With Pseudo-conductive Hearing Loss. Issue 3 (March 2020) - Hilly, Ohad; Sokolov, Meirav; Finkel, Reut Beck; Zavdy, Ofir; Shemesh, Rafael; Attias, Joseph
Abstract : Objective: The role of bilateral bone conduction amplification in patients with bilateral conductive hearing loss is unclear because cranial attenuation is usually considered negligible, and both cochleae can be stimulated with similar efficacy by each device. The aim of the study was to determine if bilateral bone-conduction hearing aids can improve hearing in noise in a homogeneous group of normal-hearing subjects with bilateral pseudo-conductive hearing loss. Study Design: Prospective, comparative. Setting: Department of Communication Sciences and Disorders in University of Haifa, Israel. Subjects: Department of Communication Sciences and Disorders in University of Haifa, Israel. Interventions: Induction of bilateral pseudo-conductive hearing loss of more than 35 dB using earplugs and earmuffs. Main Outcome Measures: Hearing quality on blinded comparison of unilateral versus bilateral amplification with bone-conduction hearing aids under different locations of noise. Results: Unilateral and bilateral amplification had similar efficacy when both signal and noise were presented from the front. However, bilateral amplification was significantly better when signals were presented from the front and noise was presented from both sides (SNR −10: 92% vs. 84%, p = 0.001; SNR −15: 84% vs. 78%, p = 0.005). Analysis of subject responses on blinded questionnaires revealed that 81% found hearing easier with bilateral amplification. Noise was reported to be more disturbing with unilateral amplification by 55% of the subjects and with bilateral amplification, by 9%. Conclusions: Bilateral amplification with bone conduction devices can improve understanding in noise in the binaural squelch setting. Subjective improvements with bilateral bone-conduction aids included better sound quality and reduced noise disturbance. These findings are consistent with the binaural mechanism of spectral release from masking.